The Role Of Human Resources Competency On SMEs Performance In Timor – Leste - Egidio da Costa; Niu Xiong ying (Eduvest - Journal of Universal Studies, 2021)
Small and medium enterprises (SMEs) play a large role in the economic development of each country. This can be seen from their contribution to the Gross Domestic Product (GDP). In addition, the existence of impact on the development of several countries, especially small and developing countries. This study was conducted with the aim of exploring the influence of skills, knowledge and abilities on the performance of SMEs with a quantitative approach. The population in this study was SMEs domiciled in Dili, Timor-Leste and the sampling Method was simple random sampling technique. The data collection was conducted by distributing questionnaires to 250 units of SMEs business owners and managers. The measurement scale Used was a Likert scale. The data were analyzed using SPSS version 23 with multiple regression analysis. The results of the F test (Simultaneous) analysis show that the skills (X1), knowledge (X2) and ability (X3) have positive and significant effects on SMEs’ performance (Y). While t test (Partial) results show skills is positive, but Do not significantly influence SMEs performance while knowledge and abilities show positive and significant effects on SMEs performance.